Effects of antimicrobial metal nanoparticles on characteristics and function properties of mouse mesenchymal stem cells - Echalar, Barbora; Dostalova, Dominika; Palacka, Katerina; Javorkova, Eliska; Hermankova, Barbora; Cervena, Tereza; Zajicova, Alena; Holan, Vladimir; Rossner, Pavel (Toxicology in vitro, 2023)
Nanoparticles (NPs) have a wide use in various field of industry and in medicine, where they represent a promise for their antimicrobial effects. Simultaneous application of NPs and therapeutic stem cells can speed up tissue regeneration and improve healing process but there is a danger of negative impacts of NPs on stem cells. Therefore, we tested effects of four types of metal antimicrobial NPs on characteristics and function properties of mouse mesenchymal stem cells (MSCs) in vitro. All types of tested NPs, i.e. zinc oxide, silver, copper oxide and titanium dioxide, exerted negative effects on the expression of phenotypic markers, metabolic activity, differentiation potential, expression of genes for immunoregulatory molecules and on production of cytokines and growth factors by MSCs. However, there were apparent differences in the impact of individual types of NPs on tested characteristics and function properties of MSCs. The results showed that individual types of NPs influence the activity of MSCs, and thus the use of metal NPs during tissue regeneration and in combination with stem cell therapy should be well considered.
Keywords: Metal nanoparticles; Animals; Cytokine production; kovové nanočástice; Gene expression; mezenchymální kmenové buňky; Nanoparticles; Wound Healing; buněčná diferenciace; antiinfekční látky; Dose-dependent toxicity; Mice; Anti-Infective Agents; Metal Nanoparticles; nanočástice; myši; Mesenchymal Stem Cells; Mesenchymal stem cells; hojení ran; Cell Differentiation; zvířata